Cognitive behavioral therapy improves diverse profiles of depressive symptoms in Parkinson's disease. (4th March 2019) - Dobkin, Roseanne D.; Mann, Sarah L.; Interian, Alejandro; Gara, Michael A.; Menza, Matthew
Abstract : Objective: Depression is among the most common and debilitating nonmotor complaints in Parkinson's disease (PD), yet there is a paucity of controlled research to guide treatment. Little research has focused on the extent to which specific depressive symptom profiles may dictate unique clinical recommendations to ultimately improve treatment outcomes. The current study examined the impact of cognitive behavioral therapy (CBT) on different types of depressive symptoms in PD. It was hypothesized that the cognitive (eg, guilt, rumination, and negative attitudes towards self) and behavioral (eg, avoidance and procrastination) symptoms targeted most intensively by the treatment protocol would show the most robust response. The extent to which stabilized antidepressant use moderated specific symptom change was examined on an exploratory basis. Method: Eighty depressed people with PD participated in a randomized controlled trial of CBT plus clinical management, versus clinical management only. Hamilton Depression Rating Scale (HAMD) and Beck Depression Inventory (BDI) subscale scores, reflecting depressive symptom heterogeneity in PD, were the focus of this investigation. Results: CBT response was associated with significant improvements in mood, sleep, anxiety, and somatic symptoms (HAMD), and negative attitudes toward self, performance impairment, and somatic symptoms (BDI). As hypothesized, the largest effect sizes were observed for cognitive and behavioral (vs somatic) symptoms of depression. Stabilized antidepressant use moderated the effect of CBT on somatic complaints (HAMD and BDI). Conclusions: CBT may improve a diverse array of depressive symptoms in PD. Cognitive and behavioral (vs somatic) symptoms showed the greatest change. Combining CBT with antidepressants may help optimize the management of somatic complaints in depression in PD (dPD).